Review of the genus Rhaphiocerina Lindner (Diptera: Stratiomyinae), with description of a new species - Li, Zhu; Yang, Ding; Zhang, Tingting (Zootaxa, 2016)
Genus Rhaphiocerina is revised and discussed. The known species R. hakiensis (Matsumura, 1916) is redescribed and illustrated. A new species, Rhaphiocerina chinensis sp. nov., is described and illustrated. A key is presented to separate the known genera in Stratiomyinae from China.